Surface preparation of metal films by gas cluster ion beams using organic acid vapor for Cu–Cu bonding. (1st June 2022) - Hanahara, S.; Takeuchi, M.; Toyoda, N.
Abstract: Surface-activated bonding (SAB) of Cu by gas cluster ion beam (GCIB) irradiation with acetic acid vapor was studied. GCIB irradiation realizes surface smoothing and surface reaction enhancement without severe damage. Therefore, it is promising for SAB. In this study, acetic acid vapor was introduced during Ar-GCIB irradiation to assist the removal of surface oxides on the Cu surface. XPS results showed that Cu(OH)2 was effectively removed by reaction with adsorbed acetic acid, and there was no residue by acetic acid adsorption. In addition, surface roughness decreased by Ar-GCIB irradiation with acetic acid because of the preferential removal of protrusion. Preliminary bonding experiments showed an increase of Cu–Cu bond strength by Ar-GCIB irradiation with acetic acid vapor.